The importance of antioxidant micronutrients and vitamins in pregnancy - Mistry, Hiten D.; Williams, Paula J. (Hindawi Publishing Corporation, 2011)
Pregnancy places increased demands on the mother to provide not only adequate nutrition to support her own health but also to enable the growth and development of the conceptus. A key role of a number of micronutrients and vitamins is their function as essential cofactors for or themselves acting as antioxidants. Oxidative stress is generated during normal placental development however expression of antioxidant enzymes within the placenta provides protection from undue damage. However, when supply of these antioxidant associated micronutrients is limited, antioxidant protection can be reduced, culminating in oxidative stress within both the placenta and the maternal circulation resulting in adverse pregnancy outcomes. The present literature review was prepared to summarise current understanding of the importance of micronutrient antioxidants in pregnancy. Comprehensive literature searching was performed using PubMed and Google Scholar. Sensitive search strategies were combined with relevant medical subject headings and text words.’ This review summarises the role of antioxidant micronutrients in healthy and pathological pregnancy, emphasising the need for further research in this area.